176k views
4 votes
Please help ASAP!!!!!​

Please help ASAP!!!!!​-example-1

1 Answer

0 votes

Answer: OPTION C

Explanation:

Complete the square:

Having the equation in the form
ax^2+bx=c, you need to add
((b)/(2))^2 to both sides of the equation:

You can identify that "b" in the equation
x^2+6x=5 is:


b=6

Then:


((6)/(2))^2=3^2

Add this to both sides:


x^2+6x+3^2=5+3^2

Rewriting, you get:


(x+3)^2=14

Solve for "x":


x+3=\±√(14)\\\\x+3=\±√(14)\\\\x=\±√(14)-3

Then, the solutions are:


x=-3+√(14)\ or\ x=-3-√(14)

User Aaron Bonner
by
5.1k points